Activation of the microglial P2X7R/NLRP3 inflammasome mediates central sensitization in a mouse model of medication overuse headache - Wang, Yanyun; Dong, Liang; Zhang, Yun; Zhang, Yixin; Qin, Guangcheng; Zhang, Dunke; Chen, Lixue; He, Wei; Zhou, Jiying (Frontiers in Molecular Neuroscience, 2023)
Background Excessive use of headache treatments often leads to the development, progression and exacerbation of primary headache, which is defined as medication overuse headache (MOH). A significant pathophysiological mechanism of MOH is central sensitization. Recent evidence suggests that central sensitization in chronic headache is a result of inflammatory responses mediated by microglial activation in the trigeminal nucleus caudalis (TNC). However, it is unknown whether microglial activation has an impact on the central sensitization of MOH. Accordingly, the goal of this research was to determine how microglial activation and the P2X7R/NLRP3 inflammasome signaling pathway in the TNC contribute to the pathogenesis of MOH. Methods Repeated intraperitoneal injection of sumatriptan (SUMA) was used to establish a mouse model of MOH. Basal mechanical hyperalgesia was evaluated using von Frey filaments. As central sensitization biomarkers, the c-Fos and CGRP expression levels were measured by immunofluorescence analysis. We estimated the expression of microglial biomarkers (Iba1 and iNOS) within the TNC by qRT-PCR, western blotting and immunofluorescence analysis. To elucidate the effect of microglial activation and the P2X7/NLRP3 signaling pathway on central sensitization in MOH, we evaluated whether the microglia-specific inhibitor minocycline, the P2X7R-specific antagonist BBG and the NLRP3-specific inhibitor MCC950 altered SUMA-caused mechanical hyperalgesia. Furthermore, we examined c-Fos and CGRP expression within the TNC following individual injections of these inhibitors. Results Repeated SUMA injection induced basal mechanical hyperalgesia, increased c-Fos and CGRP levels, and activated microglia within the TNC. Inhibiting microglial activation with minocycline prevented the emergence of mechanical hyperalgesia and cut down c-Fos and CGRP expression. Immunofluorescence colocalization analysis revealed that P2X7R was predominantly co-localized with microglia. The levels of P2X7R and the NLRP3 inflammasome were elevated by repeated SUMA injection, and blocking P2X7R and NLRP3 inhibited mechanical hyperalgesia and cut down c-Fos and CGRP expression within the TNC. Conclusion Based on the current findings, inhibiting microglial activation could reduce central sensitization caused by chronic SUMA treatment via the P2X7R/NLRP3 signaling pathway. The clinical management of MOH may benefit from a novel strategy that inhibits microglial activation.